Development of an Accounting Recording System for Zahrabomba Food Business - Anggrya Ningsih; Anita Anita (ConCEPt - Conference on Community Engagement Project, 2025)
This community service project aims to address the absence of structured and reliable accounting recording system in Zahrabomba, a micro-scale culinary business specializing in donuts and bomboloni. The lack of systematic documentation had caused difficulties in monitoring inventory, calculating production costs, and generating accurate financial reports, which in turn limited the owner’s ability to make informed business decisions. To resolve this issue, the project adopted a participatory approach involving direct observation, interviews, needs assessment, and system design tailored to the business’s operational characteristics. The intervention resulted in the development of an integrated accounting recording system covering chart of accounts, standardized transaction forms, procedures for inventory usage, sales recording, expense recognition, and the preparation of simple financial reports. The implementation of the system improved the accuracy, consistency, and traceability of financial information, enabling the owner to better evaluate profitability and manage resources. This project provides new insights into the importance of practical, easy-to-use accounting tools for micro culinary enterprises that often lack formal financial literacy. Future initiatives are recommended to include the digitalization of the system, training in basic financial analysis, and periodic evaluation to ensure long-term sustainability of the accounting practices.